Kepemimpinan Transformasional dalam Prespektif Pendidikan Islam - Fajar Ramadhani Mashuri (UIN Mataram, 2020)
This paper aims to discuss Islamic educational leadership, specifically describing transformational leadership that is applied in Islamic education. The author uses the study of literature as an attempt to embody the reader regarding the current issues of Islamic education leadership. The current condition of Islamic education in Indonesia needs to be discussed because it has been through a process of acculturation between traditional and modern culture. After experiencing several obstacles, Islamic education institutions are now able to compete in the global era. Of course, the person who is capable of making changes and advancements in Islamic education institutions here is the leader, and as a result we can see that today there are various kinds of Islamic educational institutions in Indonesia. With a historical concept that preserves traditional culture that is still relevant and accepts new cultures that are suitable (read: transformation) with the needs of Islamic educational institutions.